Adaptação de um modelo simplificado para verificação da influência da geometria urbana na formação de ilha de calor noturna - Nakata Osaki, Camila Mayumi (Universidade Federal de São Carlos, 2016)
Nocturnal heat island formation is a prominent phenomenon in research of urban planning and thermal comfort. This phenomenon is the result of the influence of urbanization characteristics, which alter the energy balance of the cities, and is characterized by an increase in air temperature, from the periphery to the center of cities. The heat island has as a major cause, the urban geometry. In this context, the model proposed by Oke, in 1981, became a reference in the area because of its importance in analytical studies of relation between urban geometry and the formation of heat islands. This research aims to determine the role of urban geometry in the formation of nocturnal heat islands, from the adaptation of a simplified model for a computational simulation tool GIS (Geographic Information System). The methodological procedures have steps: study of theoretical and numerical base, developing a calculation algorithm and its incorporation into the GIS platform, data monitoring for calibration (validation) and simulation. The measured data for the tool validation demonstrated an increasing trend of heat island with increasing H/W ratio (height/width) canyon, but there are different behavior for different ranges of roughness length (Z0). The developed tool, THIS (Tool for Heat Island Simulation), was used in simulation of different scenarios, which showed that urban canyons of greater roughness result in heat island values twice lower compared to the canyons of lower roughness, for the same H/W ratio. The development of THIS tool expands the possibilities of simulations to forecast heat islands to different climatic conditions and suggests further discussion on the influence of different urban geometry settings in the formation of heat island.
Keywords: Geometria urbana; Ilha de calor urbana; Simulação computacional; SIG; Urban heat island; Urban geometry; Computational simulation; GIS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS